OP0170 Achieving ASDAS-CRP major improvement and inactive disease in patients with ankylosing spondylitis after treatment with golimumab is associated with normalized health related quality of life: Two-year results from the go-raise trial. (23rd January 2014) - van der Heijde, D.; Deodhar, A.; Braun, J.; Mack, M.; Hsu, B.; Gathany, T.; Han, C.; Inman, R.
Abstract : Background: Significantly greater improvements in health-related quality of life (HRQoL) and reduction of impact of disease on work productivity were observed in patients (pts) with ankylosing spondylitis (AS) treated with golimumab when compared with placebo at weeks 14 and 24. Objectives: This analysis examined association of ASDAS major improvement and inactive disease with these improvements and the maintenance over two years. Methods: In the GO-RAISE study, 356 pts with definite AS according to the modified NY criteria were randomly assigned in a 1.8:1.8:1 ratio to receive subcutaneous injections of golimumab 50 or 100 mg or placebo every 4 weeks. HRQoL was assessed using the Physical Component Summary (PCS) and Mental Component Summary (MCS) of the SF-36. Self-reported employability data, defined as currently working or able to work if a job is available, were collected. Impact of disease on productivity in daily work, school or home was assessed using a visual analogue scale (0-10), with higher values indicating greater impact. ASDAS (based on CRP) inactive disease was defined as a score of <1.3 and major improvement was defined as an improvement from baseline ≥2. An ANOVA on van der Waerden normal scores was used for numeric comparisons and chi-square tests for dichotomous comparisons. Results: At weeks 14 and 24 the combined golimumab groups had greater median improvements in ASDAS scores compared with placebo (1.6 vs. 0.4 and 1.7 vs. 0.3, respectively, p<0.001 for both). At weeks 52 and 104, when all pts received golimumab, all groups had comparable improvements in ASDAS, ranging from 1.9 to 2.3. For all pts, 33.9% and 41.6% achieved ASDAS inactive disease at week 52 and 104. Pts with major improvement for these time points were 49.1% and 52.9%. For pts achieving ASDAS inactive disease at weeks 52 and 104, 57.1% and 65.5%, respectively, had PCS ≥50. Inactive disease pts had 64.8% and 74.14% with MCS ≥50. Pts with ASDAS major improvement had 37.9% and 48.3% with PCS ≥50 and 62.1% and 65.31% with MCS ≥50 for these time points. Improvements in productivity were greater for pts with ASDAS inactive disease compared with non-inactive disease at weeks 52 and 104 (5.8 vs. 2.9 and 5.8 vs. 3.1, p<0.001 for both). Similar results were achieved for ASDAS responders compared with non-responders (5.4 vs. 2.4 and 5.8 vs. 2.6, p<0.001 for both). At baseline 40 pts were unemployable because of AS. At week 52, 6 of the 16 (37.5%) pts who achieved inactive disease regained employability, while 11 of the 16 (73.3%) pts who had major improvement regained employability. At week 104, 7 of the 18 (38.9%) pts who achieved inactive disease regained employability, while 13 of the 18 (72.2%) pts who had major improvement regained employability. Conclusions: Achieving ASDAS inactive disease or major improvement in pts with AS after treatment with golimumab is associated with improvements in HRQoL and productivity. A trend towards regaining employability was observed for pts with clinical improvements, but this association would need to be substantiated in larger studies. Disclosure of Interest: D. van der Heijde Grant/Research support from: Investigators for Janssen Research & Development, LLC sponsored clinical study, A. Deodhar Grant/Research support from: Investigators for Janssen Research & Development, LLC sponsored clinical study, J. Braun Grant/Research support from: Investigators for Janssen Research & Development, LLC sponsored clinical study, M. Mack Employee of: Janssen Research & Development, LLC, B. Hsu Employee of: Janssen Research & Development, LLC, T. Gathany Employee of: Janssen Global Service, LLC, C. Han Employee of: Janssen Global Service, LLC, R. Inman Grant/Research support from: Investigators for Janssen Research & Development, LLC sponsored clinical study